FACTORS INFLUENCING THE QUALITY OF DRINKING WATER FROM VENDING MACHINES IN THE INNER CITY OF BANGKOK - Kita, Akemi; Sihabut, Tanasri; Tantrakarnapa, Kraichat (Public Health of Indonesia, 2020)
Objective: To investigate coliform contamination in drinking water from vending machines in the Rajvithi area of Bangkok.Study Design: Cross-sectional studyMethods: Associated environmental factors were observed and self-administered questionnaires conducted. In total, 123 drinking-water samples were collected to test coliform bacteria contamination.Results: Coliform bacteria were detected in 28.5% of samples. Links were found between coliform contamination and filter cleaning practices in 57 maintenance persons' responses. Filters cleaned < 3 times per year were at higher risk of coliform contamination (OR 14.49, 95% CI 1.76-125.00). A negative association was found between coliform contamination and vending-machine filters' being cleaned within 100 days (OR 0.21, 95% CI 0.05-0.83).Conclusion: A negative association was found between coliform contamination and vending-machine filters' being cleaned within 100 days (OR 0.21, 95% CI 0.05-0.83). These results emphasized the importance of effective vending-machine maintenance and monitoring drinking-water quality.